2021
DOI: 10.3390/plants10030446
|View full text |Cite
|
Sign up to set email alerts
|

Priming Maritime Pine Megagametophytes during Somatic Embryogenesis Improved Plant Adaptation to Heat Stress

Abstract: In the context of global climate change, forest tree research should be addressed to provide genotypes with increased resilience to high temperature events. These improved plants can be obtained by heat priming during somatic embryogenesis (SE), which would produce an epigenetic-mediated transgenerational memory. Thereby, we applied 37 °C or 50 °C to maritime pine (Pinus pinaster) megagametophytes and the obtained embryogenic masses went through the subsequent SE phases to produce plants that were further subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 81 publications
2
18
3
Order By: Relevance
“…Thus, needles of M28 plants showed significantly higher contents of ABA and total CK, mainly of CK bases and glucosides, and of cZand tZ-types, while M18 plants accumulated mainly iP-types, and both M18 and M28 plants showed higher contents of DZ-types. Higher basal levels of ABA, IAA, and CKs were also observed in primed maritime pine plants studied in our previous work, in which short temperature treatments at 37 or 50 • C were applied during the induction phase of the SE propagation protocol [18]. Variation in the hormone profiles of plants derived from somatic embryos matured at different temperatures resulted in significant coefficients of correlation between basal levels of ABA and total CKs (ρ = 0.804, p = 0.002); in addition, the total CK contents correlated with the content of active CK bases (ρ = 0.719, p = 0.001).…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…Thus, needles of M28 plants showed significantly higher contents of ABA and total CK, mainly of CK bases and glucosides, and of cZand tZ-types, while M18 plants accumulated mainly iP-types, and both M18 and M28 plants showed higher contents of DZ-types. Higher basal levels of ABA, IAA, and CKs were also observed in primed maritime pine plants studied in our previous work, in which short temperature treatments at 37 or 50 • C were applied during the induction phase of the SE propagation protocol [18]. Variation in the hormone profiles of plants derived from somatic embryos matured at different temperatures resulted in significant coefficients of correlation between basal levels of ABA and total CKs (ρ = 0.804, p = 0.002); in addition, the total CK contents correlated with the content of active CK bases (ρ = 0.719, p = 0.001).…”
Section: Discussionsupporting
confidence: 70%
“…De Diego et al [51] also reported high levels of proline in radiata pine after recovery of a drought stress treatment, suggesting the possible implication of this metabolite in improving tolerance against future stress situations. In a previous work, we demonstrated that heat priming (50 • C) during SE induction improved performance under heat stress in Pinus pinaster, since primed plants showed better osmotic adjustment and higher increases in CKs, chlorophyll, soluble sugars, and starch contents, and their photosynthesis rates were less affected [18].…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Furthermore, HSPs are closely involved in cellular protection, its structures and responses to heat stress being highly conserved amongst several organisms [29,56]. According to this, in maritime pine, when heat priming was performed at immature megagametophytes through SE, similar levels of expression were observed in primed and control EMs for HSP70 and SOD, but the expression of HSP70 at the derived in vitro somatic plants was higher in control plants [57]. In P. radiata, the gene coding for a heat shock protein (HSP20) was down-regulated in proliferating EMs and somatic plants coming from EMs initiated at high temperatures [42].…”
Section: Discussionmentioning
confidence: 99%